Estimulación de la lectura y la escritura a través del mural artístico (2019)
The research project Motivation of reading and writing processes through mural painting was undertaken in a public school called I.E.D. Técnica Bilingüe Jorge Nicolás Abello in Barranquilla, Colombia. It was carried out by 4 teachers of elementary education and the study population was a group of 144 students from second grade C. Qualitative research was implemented, based on the action research method and the socio-critical paradigm in order to identify the strategies utilized by teachers in elementary to motivate the reading and writing process in the study group. Although teachers use diverse strategies to motivate reading and writing, the data analysis showed that there are needs regarding to teachers’ methodology, use of didactic resources and appropriation of learning environment to facilitate the teaching and learning process. Based on the results it was created a new pedagogical proposal to improve elementary teachers’ methodology through outdoor learning and using the artistic mural as a didactic resource. As a result of this study, it was created the proposal called “Motivation of reading and writing processes through mural painting”, a didactic guide that may be a reference in the education field